Própolis no desempenho produtivo e qualidade de ovos de poedeiras Isa Label - Costa, Monik Kelly de Oliveira (Universidade Federal Rural do Semi-Árido, 2015)
The objective was to evaluate the influence of the addition of propolis extract in diets with different levels of crude protein on growth performance and quality of laying eggs Isa Label created in high temperature environment. For this, we used 104 birds distributed in a completely randomized design in a 2x2 factorial design (CP level and propolis extract) being four diets, one control and another with 5% reduction of crude protein, each with and without the addition of 0.70% of propolis extract with 13 repetitions and two birds each. Were evaluated: egg production rate, feed conversion, absolute and relative weight of yolk, albumen and shell, height and width of the egg, specific gravity, yolk color, eggshell thickness, Haugh unit, albumen and yolk index. Propolis extract (0.70%) provided increase of egg production rate and improves feed conversion, to the crude protein level of 17.70%, and promote coloring sharper yolk. Therefore, the level of 0.70% hydroalcoholic extract of propolis can be used in diets for laying hens Isa label as it improves desirable characteristics such as egg production rate, feed conversion and yolk color when the feed has protein level of 17 7%. And the protein level of 16.82% can be used for laying Isa Label without prejudice to on broiler performance
Propolis on productive performance and quality eggs of hens laying isa label
Keywords: poultry; Laying semi-heavy; Crude protein - feed; Feed birds - alternative additives; Isa Label - quality eggs; Avicultura; Poedeiras semipesadas; Proteína bruta - ração; Ração de aves - aditivos alternativos; Isa Label - qualidade de ovos; CIENCIAS AGRARIAS::MEDICINA VETERINARIA